ERG expression in prostate cancer: The prognostic paradox. Issue 15 (29th August 2014) - Taris, Michael; Irani, Jacques; Blanchet, Pascal; Multigner, Luc; Cathelineau, Xavier; Fromont, Gaelle
<x xml:space="preserve">Abstract</x> BACKGROUND TMPRSS2/ERG fusion resulting in ERG overexpression occurs in 30 to 50% of prostate cancer (PCa) in Caucasian patients, but its prognostic relevance remains controversial. In the present study, we investigated ERG expression in all stages of PCa progression, and evaluated the prognostic impact of ERG status in clinically localized PCa (CLC) and in castration resistant disease (CRPC). METHODS ERG and AR expressions were evaluated by immunohistochemistry on tissue microarrays containing samples of high grade PIN (n = 57), CLC surgically treated (n = 299, including 185 Caucasians and 114 African‐Caribbeans), metastases (n = 17), and CRPC (n = 41). RESULTS In Caucasians, ERG expression significantly increased from high grade PIN (17.5%) to pT2 (27%) and pT3 CLC (43%), then to metastases (53%). In CLC, stainings for ERG and AR were correlated, and ERG expression was less frequent in African–Caribbeans compared to Caucasians (11.5% vs. 33%). In Caucasians CLC, ERG was associated with longer recurrence free survival, after adjusting for classical prognostic markers. In CRPC, ERG was expressed in 29% of cases, and was associated with a longer overall survival. CONCLUSIONS Our results confirm that ERG expression is less frequent in PCa from patients of African descent. Although ERG expression increases during PCa natural history, positive ERG status is associated with better outcome in both CLC and CRPC. This paradox could be explained in part by the fact that ERG expression is AR dependant, then ERG positive cancers are likely to progress in a rich androgen environment, with a better response to androgen suppression. Prostate 74:1481–1487, 2014. © 2014 Wiley Periodicals, Inc.